Wetland restoration by natural succession in abandoned pastures with a degraded soil seed bank. Issue 6 (15th May 2017) - Morimoto, Junko; Shibata, Masatoshi; Shida, Yuichiro; Nakamura, Futoshi
Abstract: Natural restoration of historical wetland plant communities in fallow fields with a degraded seed bank has been assumed to be possible only if source populations of the target species are present adjacent to the abandoned fields and a high density of suitable microsites is available. However, few studies have monitored both factors simultaneously and verified this assumption. We hypothesized that plant communities that are similar to historical wetlands, including back marshes, back swamps, and bogs, will reestablish in abandoned pasturelands in cases when (1) gaps for new recruitment emerge, followed by the decline of pastures; and (2) seeds with longevity are supplied from the surrounding remnant plant communities of wetlands. We conducted a survey of vegetation and microsites in pastures, abandoned pastures, and reference wetlands followed by structural equation modeling to verify our hypothesis for the natural restoration of Phragmites australis–Phalaris arundinacea and Alnus japonica–Spiraea salicifolia communities. These communities represent historical back marshes and back swamps along a river. However, our hypothesis was not verified for the natural restoration of Vaccinium oxycoccos–Sphagnum spp. communities, which represent plant communities in historical bogs grown on acidic peat that are maintained by rainfall and fog. Our findings partly support our hypothesis that decline in pastures creates gaps and that cumulative seed dispersal from nearby remnant wetlands allows the original wetland plant communities to regenerate. Further case studies are needed to determine how the natural restoration of bog plant communities occurs.